A Study of Safety Coefficient Determination and Support Parameter Optimization Based on Vulnerability Preevaluation - Minglei Zhang; Linsheng Gao; Yue Yang; Yidong Zhang; Ming Ji (Shock and Vibration)
The preevaluation to the vulnerability of the surrounding rocks is proposed as one of the reliable indicators of the safety coefficient of gateway support and a foundation to optimize the support design parameters. In this study, taking the surrounding rocks, stress, geological environment, and service time into consideration, the safety coefficient is determined based on the vulnerability scores calculated by the vulnerability preevaluation model of the surrounding rock. Applying the safety coefficient to the instability evaluation of the composite rock-bolt bearing structure, the strength required to maintain the stability of the gateway is calculated, which further provides references and guidance to the optimization of the anchor support parameters. This method has been successfully adopted by the GuCheng coal mining project in N1303 tailgate to strengthen the anchor-bolt structure in the roof watering area especially the main inclined shaft. Applying more accurately calculated strength to the anchor-bolt structure can effectively avoid the issue of overcompensation, thus reducing the cost and increasing the driving speed. Furthermore, this method provides insights into optimizing design parameters of the gateway. This method provides a reliable basis for the optimization design of bolt support parameters in coal mine gateway.